Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00223-017-0367-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Bone: Pharmacologically Induced Diabetes has Deleterious Effect on Bone in Growing Obese Rats

Abstract: Metabolic syndrome and osteoporosis share similar risk factors. Also, patients with diabetes have a higher risk of osteoporosis and fracture. Liver manifestations, such as non-alcoholic steatohepatitis (NASH), of metabolic syndrome are further aggravated in diabetics and often lead to liver failure. Our objective was to create a rat model of human metabolic syndrome and determine the long-term impact of early-onset T1D on bone structure and strength in obese growing rats. Male rats were given either standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…There is growing evidence supporting that DM may result in disturbance of bone metabolism [6]. Several studies [7,8] demonstrated that DM induced bone loss and reduced bone mechanical properties with a decreased osteoblastic bone formation rate.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence supporting that DM may result in disturbance of bone metabolism [6]. Several studies [7,8] demonstrated that DM induced bone loss and reduced bone mechanical properties with a decreased osteoblastic bone formation rate.…”
Section: Introductionmentioning
confidence: 99%
“…D levels were calculated in lab rats with renal failure that were administered hydrochloric acid in order to produce metabolic acidosis and non-acidotic uremic controls; there was no significant difference in 1,25-Vit. D levels throughout these groups 32,33 .…”
Section: The Impact Of Metabolic Acidosis On Bone Regulatory Hormonesmentioning
confidence: 89%
“…The protein fraction of lipoproteins is called apolipoprotein (Apo) (Mooser et al, 1997), and has important physiological functions in lipoprotein metabolism (Florea et al, 2022). Apolipoprotein B is synthesized in the liver (Bell et al, 2011) and is the main structural protein of LDL (Yaseen et al, 2021), accounting for most of the total protein content of LDL, with its measurement directly reflecting LDL levels (Sun et al, 2020). Elevated obesity (weight overload) leads to elevated levels of apolipoprotein B in the blood (Manapurath et al, 2022), which decrease with exercise, vegetarianism, and hypolipidemia (Hostmark et al, 1993;Gao et al, 2018;Stanton et al, 2022).…”
Section: Discussionmentioning
confidence: 99%